Strategic management : awareness and change - Thompson, John L. (London ; Melbourne : International Thomson Business Press, 1997)
This book is about: Strategic management; Strategic awareness; The content of competitive strategies; The content of corporate strategy; Strategy implementation, change and control;...
Keywords: Management; Strategic planning; Industrial management; Strategic planning